Criticizing “tradition” in the context of Eugen Drewermann’s “Psyhoanalytic exegesis” - Elizaveta Reshchikova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The paper examines the functions of “tradition” in the Catholic critical discourse basing on the works of one of the most provocative catholic authors of the second half of the 20th century. The meaning of “tradition” in Catholic theology seems to be rather vague; however, in the works of the 20th century theologians it is possible to trace two most general aspects of the concept: tradition as transcendent truth, given by God, and tradition as order, custom or teaching, created by people, historical in its character. The transcendent core of tradition has a strong positive connotation, while its historical aspect can be subject to critique. The two aspects are used both by the adherents of a conservative policy, and by the supporters of church reform, which testifies to a certain flexibility of the term. Eugen Drewermann, one of the most notable modern critics of the Catholic Church, uses the notion in a negative sense, which magnifies the critical potential of his argument. This critical effect does not result singularly from the definition of “tradition” Drewermann gives in his texts. In order to explicate the specific way the author uses the term and to reconstruct its critical potential, the article analyzes the notion of “tradition” functionally: basing on the author's three-volume thesis, Structures of Evil, where he combined biblical exegesis with current psychoanalytic knowledge, and Depth Psychology and Exegesis, the book where Drewermann continues to develop his innovative exegetical method. This approach makes it possible to trace how the notion acquires negative connotations: by excluding the transcendent aspect from the field of its denotations, by discussing religion in terms of psychoanalysis, as well as by linking tradition to such negatively connoted terms as “fear”, “neuroticism”, “external” and contrasting it to the “objective”, “internal”, “natural” and “true”. Eugen Drewermann’s critical interpretation of tradition based on the psychological understanding of religion in fact deprives Christianity of its transcendent origin and delegitimizes the modern institutional form of Catholicism: which allows the author to radicalize the question of the extent to which the Church is liable to change.